PROTECTION OF CIVILIAN INFRASTRUCTURE IN CONTEMPORARY ARMED CONFLICTS: A HUMANITARIAN LAW STUDY ON ATTACKS AGAINST WATER AND ENERGY FACILITIES IN GAZA AND UKRAINE - Frahma, Elen Anedya (CERED Indonesia Institute, 2025)
Contemporary armed conflicts exhibit increasingly complex patterns of attacks on vital civilian objects, including water and energy infrastructure. This study critically examines the legal protection of non-military civilian facilities such as hydroelectric power plants, reservoirs, and clean water systems from the perspective of International Humanitarian Law (IHL). Using a literature review method based on Human Rights Watch reports and international journal articles published since 2022, the research explores two primary case studies: the 2023 attack on the Dnipro Hydroelectric Power Plant in Ukraine and the destruction of clean water systems in Gaza during 2023–2024. The analysis reveals that both attacks potentially violate fundamental IHL principles, such as distinction and proportionality. Furthermore, the study identifies a normative gap in the explicit protection of vital civilian facilities that directly impact civilian survival. These findings underscore the urgent need for stronger enforcement and normative reform within international legal frameworks to ensure the protection of civilian infrastructure in times of conflict.